Pemasaran Pesantren melalui Workshop Digital Marketing: Mempromosikan Program Tahfizh melalui Instagram - Afif Alfiyanto; Silahuddin; Mahdi; Muhammad Ghazali; Fitri Hidayati (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Pesantren, as Islamic educational institutions in Indonesia, play a crucial role in teaching the Qur'an through tahfizh (Qur’anic memorization) programs. However, a key challenge lies in promoting these programs to the wider public, particularly in the digital era. This community engagement project aimed to provide digital marketing training through a workshop, focusing on the use of Instagram to promote tahfizh programs. The workshop was attended by pesantren administrators and covered essential topics such as digital marketing fundamentals, creative content creation, and the use of Instagram features—including photos, videos, and Instagram Stories—to attract public attention. The results showed a significant improvement in participants’ understanding of Instagram as a promotional tool, with 85% reporting increased confidence in using the platform. Additionally, participants successfully created engaging and effective promotional content, leading to higher viewership and audience engagement. A short-term impact observed was the rise in registration for tahfizh programs at several pesantren. Nevertheless, ongoing monitoring and evaluation are needed to ensure the sustainability of these outcomes. Overall, the workshop made a positive contribution by enhancing the digital literacy of pesantren administrators and enabling them to leverage digital technology to promote their tahfizh programs.